2020
DOI: 10.1186/s12879-020-05557-8
|View full text |Cite
|
Sign up to set email alerts
|

Extensively drug-resistant Alcaligenes faecalis infection

Abstract: Background Alcaligenes faecalis is usually causes opportunistic infections in humans. Alcaligenes faecalis infection is often difficult to treat due to its increased resistance to several antibiotics. The results from a clinical study of patients with Alcaligenes faecalis infection may help improve patients’ clinical care. Methods We conducted a retrospective analysis of all patients presenting with Alcaligenes faecalis infection from January 2014 to December 2019. The medical records of all patients were re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 42 publications
0
40
1
Order By: Relevance
“…Few of the isolated endophytes of peanut in the present studies were found to be in the risk group 2 of potential pathogens like Alcaligenes faecalis, Pseudomonas otitidis, Acinetobacter junii, and Pseudomonas aeruginosa: all human pathogens (Clark et al, 2006;Balasubramani et al, 2018;Huang, 2020). However, Acinetobacter junii has been reported as a human pathogen rarely.…”
Section: Discussioncontrasting
confidence: 55%
“…Few of the isolated endophytes of peanut in the present studies were found to be in the risk group 2 of potential pathogens like Alcaligenes faecalis, Pseudomonas otitidis, Acinetobacter junii, and Pseudomonas aeruginosa: all human pathogens (Clark et al, 2006;Balasubramani et al, 2018;Huang, 2020). However, Acinetobacter junii has been reported as a human pathogen rarely.…”
Section: Discussioncontrasting
confidence: 55%
“…A. faecalis is considered as an emerging drug-resistant pathogen, causing opportunistic infections in humans. In most cases, infection generated by A. faecalis is complicated to treat because it is highly resistant to several antibiotics, such as anti-pseudomonal penicillin, cephalosporins, carbapenemics, aminoglycosides, and quinolones [ 48 ]. Currently, cases of A. faecalis infection have been identified, including cystitis, skin and soft tissue infection, pneumonia, bacteremia, meningitis, endocarditis, eye infection, peritonitis, and infectious diarrhea [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…Some of the bacteria and yeasts listed in Table 1 can cause infections in humans. These include Alcaligenes faecalis, which is often associated with local and systemic infections in humans (endocarditis, bacteremia, meningitis, endophthalmitis, skin and soft tissue infections, urinary tract infections, otitis media, peritonitis, and pneumonia) [127] and Enterobacter cloceae complex strains [128,129], as well as Candida quilliermondii and C. parapsilosis, which are in the group of six pathogenic species of yeast responsible for invasive candidiasis [130]. Most infections caused by the bacteria and yeasts listed in Table 1 are opportunistic infections.…”
Section: Alcaligenes Faecalismentioning
confidence: 99%